2020
DOI: 10.15540/nr.7.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Neurofeedback Outcomes Following qEEG Individualized Protocols for Anxiety

Abstract: In this retrospective study, researchers examined effects of quantitative electroencephalography (qEEG), individualized neurofeedback treatment protocols for anxiety. The present study includes 52 clients with 53.8% (n = 28) self-reporting as male and included two time points (pre and post). Secondary analyses utilized a subset of client data (n = 21) with measurements from three time points (pre, post, and follow-up). All clients completed qEEG and self-report assessments. Clients agreed to attend a minimum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Several studies, such as Gregory et al (2020) have suggested that the most active and transformative properties of neurofeedback protocols teach substance abuse patients to intentionally intensify the amplitude and coherent interaction of their alpha and theta brainwave frequencies. The alpha-theta neurofeedback mechanism may allow participants to better tolerate stress, anxiety, and anxiety-provoking situations, especially during initial recovery periods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies, such as Gregory et al (2020) have suggested that the most active and transformative properties of neurofeedback protocols teach substance abuse patients to intentionally intensify the amplitude and coherent interaction of their alpha and theta brainwave frequencies. The alpha-theta neurofeedback mechanism may allow participants to better tolerate stress, anxiety, and anxiety-provoking situations, especially during initial recovery periods.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol consisted of 18 sessions and two sessions per week, with each session lasting 25-30 minutes. The neurofeedback rehabilitation protocols in each session were based on SMR, Cz area (central cortex) rehabilitation (Scott et al, 2005), and Pz area (parietal cortex) alpha-theta (Gregory et al, 2020), performed in 20 min using the ProComp2 system (Thought Technology Ltd, Montreal, Canada; Scott et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest for this population, scholars have identified a positive trend in improving PTSD indicators, anxiety, and related symptoms by training alpha brainwave activity (e.g., Gregory et al, 2020;Mennella et al, 2017;Wang et al, 2019). Professionals correlate alpha oscillations with "internal reflection, brain synchrony, and peak performance," (Demos, 2019, p. 25) as well as "meditation or a deep sense of inner calm" (p. 215).…”
Section: Implications For Alpha Training and Frontal Alpha Asymmetry ...mentioning
confidence: 99%
“…University of Texas at San Antonio, San Antonio, Texas, USA Neurofeedback, or electroencephalography (EEG) biofeedback, is a therapeutic approach that integrates a client's brainwave activity to enhance and empower their specific, individualized growth through self-regulation (Demos, 2005). This modality continues to be applied to decreasing or alleviating symptoms associated with a variety of mental health concerns, including anxiety and posttraumatic stress disorder (PTSD; Gregory et al, 2020;Mennella et al, 2017;Romero et al, 2020). Traditionally, clinicians conduct neurofeedback services in person.…”
Section: James Spears and Cerise Edmondsmentioning
confidence: 99%